Ta’arruf as a philosophy of Muslim education: Extending Abu Bakr Effendi’s pragmatism, by Yusef Waghid - Terblanche, J. (South African Journal of Higher Education, 2021)
O humankind! We created you from a single (pair) of a male and a female, and made you into nations and tribes, that you may know each other (not that you may despise each other). Verily the most honoured of you in the sight of Allāh is (he who is) the most righteous of you. And Allāh has full knowledge and is well acquainted (with all things).